From Stigma to Care: Reframing Mental Health Clinics for better Accessibility - Ansari, Moin Ahmed; H. Rajput, Aatir (Journal of Pakistan Psychiatric Society, 2026)
World Health Organization (2022), report shows that more than 12% of world population suffers one or the other mental health condition, but the treatment gap remains most pronounced in low- and middle-income countries (LMICs). In Pakistan, and neighboring countries, deep rooted societal taboos, lesser mental health awareness, shortage of culturally appropriate services are the main contributing factors for this treatment. Stigma attached to mental disorders continues to be a major hinderance to accessing help, in Pakistan. As a consequence to reluctance to seeking mental health support, symptoms get worse, severity aggravates, recovery becomes more complicated. The “change of label” strategy is likely to effectively minimize psychological resistance, and increase acceptability and treatment of mental health conditions. The successful implementation of this model at Sir Cowasjee Jehangir Institute has proved that how thoughtful, relabeling and language modification can meaningfully create comfortable access and reduce barriers, without compromising on clinical standards.